Acute exposure of methylglyoxal leads to activation of KATP channels expressed in HEK293 cells - Yang Yang; Konduru Anuhya S; Cui Ningren; Yu Lei; Trower Timothy C; Shi Weiwei; Shi Yun; Jiang Chun (Acta Pharmacologica Sinica, 2016)
Yang YANG#, *, Anuhya S KONDURU, Ningren CUI, Lei YU, Timothy C TROWER, Weiwei SHI, Yun SHI, Chun JIANG* Department of Biology, Georgia State University, 24 Peachtree Center Avenue, Atlanta, GA 30302–4010, USA Aim: Highly reactive carbonyl methylglyoxal (MGO) is one of the metabolites excessively produced in diabetes. We have showed that prolonged exposure of vascular smooth muscle cells to MGO leads to instability of the mRNA encoding ATP-sensitive potassium (KATP) channel. In the present study we investigated the effects of MGO on the activity of KATP channels. Methods: Kir6.1/ SUR2B, Kir6.2/SUR2B or Kir6.2Δ36 (a truncated Kir6.2 isoform) alone was expressed in HEK293 cells. Whole-cell currents were recorded in the cells with an Axopatch 200B amplifier. Macroscopic currents and single-channel currents were recorded in giant inside-out patches and normal inside-out patches, respectively. Data were analyzed using Clampfit 9 software. Results: The basal activity of Kir6.1/SUR2B channels was low. The specific KATP channel opener pinacidil (10 µmol/L) could fully activate Kir6.1/SUR2B channels, which was inhibited by the specific KATP channel blocker glibenclamide (10 µmol/L). MGO (0.1–10 mmol/L) dose-dependently activated Kir6.1/SUR2B channels with an EC50 of 1.7 mmol/L. The activation of Kir6.1/SUR2B channels by MGO was reversible upon washout, and could be inhibited completely by glibenclamide. Similar results were observed when Kir6.2/SUR2B channels. Kir6.2Δ36 channels expressed in HEK293 cells could open automatically, and the channel activity was enhanced in the presence of MGO (3 mmol/L). Single channel recordings showed that MGO (3 mmol/L) markedly increased the open probability of Kir6.1/SUR2B channels, leaving the channel conductance unaltered. Conclusion: Acute application of MGO activates KATP channels through direct, non-covalent and reversible interactions with the Kir6 subunits. Keywords: methylglyoxal; reactive carbonyl species; ATP-sensitive potassium channel; Kir6.1; Kir6.2; Kir6.2Δ36; sulfonylurea receptor; diabetes; vascular dysfunction This study was supported by the NIH (1R211HD060959, 1R01NS073875) and the American Heart Association (09GNT2010037). Yang YANG was a Brains and Behavior fellow of Georgia State University. # Now in Center for Neuroscience & Regeneration/Rehabilitation Research, Department of Neurology, Yale University School of Medicine & Veterans Affairs Connecticut Healthcare System, USA. * To whom correspondence should be addressed. E-mail yang.yang.neurology@yale.edu (Yang YANG); cjiang@gsu.edu (Chun JIANG) Received 2013-05-06 Accepted 2013-07-21